2017
DOI: 10.1002/cam4.1024
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miRNA‐141 in breast cancer cells is associated with cell migration and invasion: involvement of ANP32E targeting

Abstract: MicroRNAs (miRNAs) regulate many cellular activities, including cancer development, progression, and metastasis. Some miRNAs are involved in breast cancer (BC) migration and invasion, thus affect patients’ prognosis. Microarray analysis was performed to compare miRNA expression in BC tissues, and results confirmed by qPCR. BC cell migration and invasion were studied in vitro with MDA‐MB‐231 cells using microplate transwell assays. miRNA targeting was investigated using luciferase assays, qPCR, and Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 35 publications
(43 reference statements)
1
51
0
Order By: Relevance
“…By analyzing the miRNA microarray data derived from TCGA, we found that high expression of miR-141-5p was associated with better OS in TNBC patients 1 (Figure 3B). According to the reported research, downregulation of miR-141-5p was associated with progression and trastuzumab resistance in breast cancer (Finlay-Schultz et al, 2015;Li et al, 2017;Han et al, 2019). Detected by qPCR analysis, miR-141-5p was downregulated in TNBC cell lines compared to that in mammary epithelial cell lines (Supplementary Figure S2A).…”
Section: Downregulation Of Circgnb1 Suppresses the Proliferation Andmentioning
confidence: 83%
See 1 more Smart Citation
“…By analyzing the miRNA microarray data derived from TCGA, we found that high expression of miR-141-5p was associated with better OS in TNBC patients 1 (Figure 3B). According to the reported research, downregulation of miR-141-5p was associated with progression and trastuzumab resistance in breast cancer (Finlay-Schultz et al, 2015;Li et al, 2017;Han et al, 2019). Detected by qPCR analysis, miR-141-5p was downregulated in TNBC cell lines compared to that in mammary epithelial cell lines (Supplementary Figure S2A).…”
Section: Downregulation Of Circgnb1 Suppresses the Proliferation Andmentioning
confidence: 83%
“…According to the bioinformatic analysis and public database, miR-141-5p was predicted as the downstream of circGNB1 and low expression of miR-141-5p was associated with an improved overall survival clinical outcome. Downregulation of miR-141 contributes to the cancer cell growth, migration, trastuzumab resistance and stem cell expansion in breast cancer (Finlay-Schultz et al, 2015;Li et al, 2017;Han et al, 2019). IGF1R is a receptor binding insulin-like growth factor with a high affinity with tyrosine kinase activity, which is highly overexpressed in most malignant tissues and enhances cell survival (Pollak, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is coordinated by several proteins and noncoding RNA molecules, partially through similar mechanisms in different malignancies (Table 1). Negative impact of hyperactivity of HOTAIR has been shown on regulation of miR-141 and miR-326 in glioma cells [56,57], as well as suppression of miR-141 in breast cancer cells [58]. Enforced transcription of HOTAIR could also promote proliferation, invasion and metastasis in gynaecological malignancies and breast cancer [59][60][61], through different mechanisms including up-regulation of BCL-W and sponging miR-206 [62].…”
Section: Hotair Aberration and Breast Cancermentioning
confidence: 99%
“…These RNAs are regulatory molecules that modulate the expression of functional genes, play an important role in many biological processes, and are expressed in a tissue-and time-specific manner. miRNAs regulate gene expression at the post-transcriptional level mainly via completely complementary or partially complementary binding to the 3' UTR of the target gene, resulting in degradation or translational repression of the target gene (2)(3)(4). Studies have shown that a variety of miRNAs are involved in malignant transformation processes, such as malignant proliferation, metastasis and recurrence, and apoptosis inhibition.…”
Section: Introductionmentioning
confidence: 99%